2016
DOI: 10.1371/journal.pgen.1006092
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multiple Proteins Coupling Transcriptional Gene Silencing to Genome Stability in Arabidopsis thaliana

Abstract: Eukaryotic genomes are regulated by epigenetic marks that act to modulate transcriptional control as well as to regulate DNA replication and repair. In Arabidopsis thaliana, mutation of the ATXR5 and ATXR6 histone methyltransferases causes reduction in histone H3 lysine 27 monomethylation, transcriptional upregulation of transposons, and a genome instability defect in which there is an accumulation of excess DNA corresponding to pericentromeric heterochromatin. We designed a forward genetic screen to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
58
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(61 citation statements)
references
References 56 publications
3
58
0
Order By: Relevance
“…Importantly, these phenotypes in the double mutant plants were reverted back to those of each single mutant by introducing either the genomic ARP6 or MBD9 constructs into the double mutants ( Figure S6), indicating that these defects were truly the result of simultaneous loss of ARP6 and MBD9 functions. These findings further support the idea that MBD9 is not a core subunit of the ARP6-containing SWR1 complex and suggest that this protein has additional functions outside of H2A.Z incorporation (Hale et al, 2016).…”
Section: Mbd9 Is Not a Core Subunit Of The Arabidopsis Swr1 Complexsupporting
confidence: 78%
“…Importantly, these phenotypes in the double mutant plants were reverted back to those of each single mutant by introducing either the genomic ARP6 or MBD9 constructs into the double mutants ( Figure S6), indicating that these defects were truly the result of simultaneous loss of ARP6 and MBD9 functions. These findings further support the idea that MBD9 is not a core subunit of the ARP6-containing SWR1 complex and suggest that this protein has additional functions outside of H2A.Z incorporation (Hale et al, 2016).…”
Section: Mbd9 Is Not a Core Subunit Of The Arabidopsis Swr1 Complexsupporting
confidence: 78%
“…ATXR5 and ATXR6 likely associate with the replication fork and are only capable of modifying the replication dependent histone variant H3.1, due to an amino acid difference between H3.1 and H3.3 at residue 31 [48]. Reverse and forward genetic studies have identified a plethora of suppressors of TE over-replication in atxr5 atxr6 , which have differential effects on the suppression of loss transcriptional silencing [41,48,49] It remains to be seen whether H3K27me1 controls heterochromatic DNA replication directly or indirectly, and also if H3K27me1 plays a role in delaying heterochromatic replication to late S-phase.…”
Section: Variation In Epigenetic Control Of Te Expression Transpositmentioning
confidence: 99%
“…This line is deficient for histone H3 lysine 27 (H3K27) monomethylase activity as a result of insertional mutations in the Arabidopsis trithorax-related protein 5 (ATXR5) and Arabidopsis trithorax-related protein 6 (ATXR6) genes (22). In atxr5 atxr6 double mutants, transposable elements are derepressed and genome instability involving heterochromatin over-replication occurs (23,24). We show that, in the course of generating the atxr5 atxr6 double mutant line, an estimated ∼2-3 Mb of the northern tip of chromosome 4 was replaced by corresponding sequences of chromosome 2, thus translocating NOR2 rRNA genes to the position of NOR4.…”
mentioning
confidence: 99%